"To get the baby out off the hook": a prospective, longitudinal, multicenter, observational study about decision making in vacuum-assisted operative vaginal delivery - Alessandro Svelato; Alis Carabaneanu; Claudia Sergiampietri; Paolo Mannella; Sara D'Avino; Caterina De Luca; Martina Bartolone; Roberto Angioli; Antonio Ragusa (BMC, 2022)
Abstract Background Since operative vaginal delivery may be risky for women and might cause neonatal complications, the aim of this study is to assess appropriateness of the procedure. This is a prospective, longitudinal, multicenter, observational study and it was conducted in three Italian Obstetric Units (Pisa, Massa Carrara and Prato). All term pregnant women, either nulliparous and multiparous, with singleton pregnancy and a cephalic fetus, with spontaneous or induced labour, requiring vacuum-assisted delivery were enrolled. Indications to operative vaginal delivery were grouped as alterations of fetal cardiotocography (CTG) patterns, delay/arrest of second stage of labour or elective shortening of second stage of labour. A board consisting of five among authors evaluated appropriateness of the procedure. Results Overall, 466 women undergoing operative vaginal deliveries were included. Cardiotocography, classified as ACOG category 2 or 3 was the indication for vacuum assisted delivery in 253 patients (54.29%). Among these, 66 women (26.1%) had an operative vaginal delivery which was then considered to be inappropriate, while in 114 cases (45.1%) CTG traces resulted to be unreadable. Conclusion Decision making process, which leads clinicians to go for operative vaginal delivery, is often influenced by shortness of time and complexity of the situation. Therefore, clinicians tend to intervene performing vacuum delivery without adopting critical analysis and without adequately considering the clinical situation. Tweetable abstract Operative vaginal delivery might be a risky procedure and should be performed only when clinically indicated and after adequate critical analysis.